Upgrading Kai-Weaved Textiles for Cultural Products of the Mae Loi Luang Community, Chiang Rai Province - Jenjai, Narong (Area Based Development Research Journal, 2020)
The purpose of this participatory action research seeks to upgrade Kai-weaved textiles for cultural products of Mae Loi Luang community, Sri Don Chai subdistrict, Theong district, Chiang Rai province. The research process is based on the implication of the late King’s philosophy entitled “Understanding, Accessibility, and Development”. The research process also employs a survey of local wisdoms on weaved textiles, the development of local products with communities, and evaluation of cultural product appropriateness. Research participants were 15 residents, which included the village head, village committee members, a women’s union director, members of textile-weaving group, and the temple’s abbot. This study revealed that Kai-weaved textiles have been inherited from the Mae Loi Luang community’s local wisdom. The Kai-weaved textile is designed with two thread-stripped weaving techniques in order to create dimensions of Kai-weaved textiles and beauty. The village’s Kai-weaved textiles reflected their ways of life and local identities, which are categorized into two types of cultural products: grandmother-like and niece-like Kai-textile dolls and Kai-stripped. The cultural product quality assessment confirmed a high appropriateness; subsequently, these cultural products raise community awareness of Kai-textile values. In summary, the project facilitated community cooperation in textile-weaving promotion, and the establishment of indigenous textile-weaving center.